The Implementation of instilling the value of Islamic education in the students of the Bukit Hidayah Malino Islamic Boarding School, Gowa Regency - Jumadi, Jumadi; Rama, Bahaking; Miro, Abbas Baco; Maryam, Maryam; Muslimin, Abdul Aziz (Universitas Pendidikan Indonesia, 2023)
Analysing the implementation of Islamic education values in the center, the actualization of the Islamic Education values, the implications of cultivating Islamic educational values on the existence of the Pondok Pesantren Bukit Hidayah Malino district of Gowa. The type of research is qualitative descriptive with a methodological approach and scientific with two sources of data: primary and secondary. Data collection through observations, interviews and documentation. Data analysis with data reduction measures, data presentation, and data verification.The results of the research show that, first, the implementation of the cultivation of Islamic educational values is carried out inside and outside the classroom both when the learning process is in progress in class as well as training, such as, study of the book, compulsory prayer, and others. Third, the implications of the cultivation of the values of Islamic education to the existence of the Pondok Pesantren Bukit Hidayah Malino district of Gowa, depicted in the religious atmosphere of the life of the pasantren as well as the presence of the activities of the Ramadan safari, and the activity of the Friday sermon by the Pasantren mansion.